Menumbuhkan Jiwa Kepemimpinan melalui Pembelajaran Soft Skill Leadership di Kota Samarinda - Dzulfa Alya; Aidah Nafisah Anwar; Indri Kristiani Matangkin; Joana Oktavia Sapan; Arwin Sanjaya; M. Tommy Fimi Putera (Yayasan Grace Berkat Anugerah, 2025)
Leadership is the ability or intellegence of a person to encourage a group of people to work together in carrying out activities aimed at achieving common goals. The webinar with the theme